If it's not what You are looking for type in the equation solver your own equation and let us solve it.
43x-7=36
We simplify the equation to the form, which is simple to understand
43x-7=36
We move all terms containing x to the left and all other terms to the right.
+43x=+36+7
We simplify left and right side of the equation.
+43x=+43
We divide both sides of the equation by 43 to get x.
x=1
| b+(2+b)=34 | | 24c-2=4+7c | | 22+6z=4+12z | | 11ab^2c^3-55a^3b^2c=0 | | 10x-9-3x=10 | | x^2-46x+180=0 | | 3=7-2y | | 1/3y+1=1/2y-3 | | 0.4(1+6c)= | | X^2-2y+x=0 | | z^6+5=8-z^6 | | 8-2x+1=9x+9 | | x+3+5=2x+4 | | 6x+3-5=40 | | 10(x+1)+8(x-1)=x-8 | | 4(2x-1)-6(3-x)=8 | | -5x+9y=-18 | | 3n^2+8=10n | | Mx+nx=x | | -2n+2n=6(1+6n)+7(1-7n) | | -5(0)+9y=-18 | | r-(-1)=9 | | 9(3n+3)=7(2n+4)+6 | | 6(x+8)-x=5x+4 | | -2(t-5)+4t=9t-6 | | 2x-9=2x-45 | | x(x+5)=(2x+10)(x-2) | | 5y-5+11x-1=9x+21 | | 15n-5=n+325 | | X^2+x=2y | | 9-(6y+2x)=8(x-y) | | 1+.80z=2+.75z |